The Emotional Intelligence and Resilience among Emerging Adults After a Romantic Breakup in Petisah Tengah - Yesika Armadani; Audrey Kikania; Reihan Kirana Zahrani; Nurgea Artha Meilani Nasution; Achmad Irvan Dwi Putra; Winida Marpaung (IJIP : Indonesian Journal of Islamic Psychology, 2026)
This investigation was orchestrated to empirically examine the relational dynamics between emotional intelligence and resilience in early adults after a breakup. The research sample amounted to 289 people who were early adult individuals who lived in Petisah Tengah and had a breakup experience, and were selected through purposive sampling. The instruments employed encompassed 23 items of the emotional intelligence scale and 36 items of the resilience scale. Data analysis was performed utilizing the Pearson Product-Moment correlation technique. The findings unveil a robust and statistically significant positive association between emotional intelligence and resilience, with a correlation coefficient of 0.674 and a p-value of 0.000 (p < 0.05). These results imply that elevated emotional intelligence is intricately linked with heightened resilience capacities, suggesting a reciprocal interplay between the two instruments.